Implantação de um sistema de injeção eletrônica programável em um motor monocilíndrico para projeto de eficiência energética - Barion, Pedro Henrique (2021)
For many years, carburetor engines were used in used in vehicles, but due to the fact that this system does not satisfactorily meet all the working conditions of the engine and the new pollutant emission standards, this technology was replaced by electronic injection. The objective of this work is to implement a programmable electronic injection system in a singlecylinder 4stroke engine that used carburetor technology. Throughout the development of the work, points such as the project of the electrical harness, the adaptation of the components of an electronic injection in the engine, as well as the initial calibration of the system will also be addressed. As result, it was possible to verify a higher efficiency of the engine with the changing of the fuel injection time, meeting the proposed objective.